Analisis Brand Engagement Pada Akun Instagram KODOMO @temankodomo - Lintang Samudera; Pratama, Agi Surya; Sakwa, Azky Dujak; Kurniasari, Ni Gusti Ayu Ketut (UHN IGB Sugriwa Denpasar, 2024)
This research discusses the strategic use of Instagram social media by children's product brand Kodomo to increase their engagement through Regina Luttrell's SoMe Circular Model. Social media plays an important role in digital communication, We Are Social stated that in January 2024, of all internet users in Indonesia aged 16-64 years, 85.3% used the Instagram application, followed by Facebook 81.6% and TikTok 73.5%. Instagram is a key platform for businesses, including Kodomo, which targets young mothers through engaging visual content. This research uses a qualitative approach to understand Kodomo's strategy in the four stages of the SoMe Circular Model: Share, Optimize, Manage, and Engage. The results show that Kodomo successfully utilizes Instagram by choosing a platform that suits the target audience. The study concludes that a structured communication strategy and a deep understanding of the audience are essential in increasing engagement on social media.